Evaluation of four protocols for the detection and isolation of thermophilic Campylobacter from different matrices - Ugarte Ruiz, María; Gómez Barrero, Susana; Porrero, M. Concepción; Álvarez, J.; García, M.; Comerón, M.C.; Wassenaar, T.M.; Domínguez, L. (My University, 2012)
Aims: To identify the optimal method for detection of thermophilic Campylo bacter at various stages in the food chain, three culture-dependent (direct plat ing, Bolton and Preston enrichment) and one molecular method (qPCR) were compared for three matrices: poultry faeces (n = 38), neck skin (n = 38) and packed fresh meat (n = 38). Methods and Results: Direct plating was compared to enrichment with either Bolton broth (ISO 10272:2006-1) or Preston broth, followed by culture on two selective agars: modified charcoal cefoperazone desoxycholate agar (mCCDA) and Campyfood agar (CFA). Direct plating on CFA provided the highest num ber of positive samples for faeces and neck skin samples. Enrichment of meat samples in Preston followed by plating on mCCDA gave significantly higher number of positives than the recommended ISO method. Real-time qPCR yielded the highest number of positive samples. Conclusion: Direct plating on CFA is optimal for Campylobacter isolation from highly contaminated samples such as faeces or neck skin. When enrichment is required for less-contaminated samples such as poultry meat, Preston broth is the best choice. The maximum of detectable cells predicted by qPCR is a sensi tive and powerful evaluation tool. Significance and impact of the study: The recommended ISO protocol had the least sensitivity, and application of this method could result in underreporting. We detected a high prevalence of Campylobacter on packed meat to be distrib uted, which suggests this is still a significant risk for consumers